2018
DOI: 10.1093/ofid/ofy130
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Mandates, Vaccination Coverage, and Exemption Rates in the United States

Abstract: BackgroundVaccination coverage among children entering kindergarten in the United States is high, but interstate variations exist. The relationship between state immunization laws and vaccination coverage has not been fully assessed. We evaluated associations of state laws on both measles, mumps, and rubella (MMR) and diphtheria, tetanus, and pertussis (DTaP) vaccination coverage and exemptions to school immunization requirements.MethodsWe conducted a retrospective, longitudinal analysis of the effect of state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…The 10th Amendment of the US Constitution is widely interpreted to reserve decisions of health policy within the rights of the state government rather than the federal government . A wide range of important and highly controversial health policies are regulated primarily at the state level, including abortion, vaccination, and physician‐assisted death, but the most vital and wide‐ranging of state‐level policies are public insurance programs, such as Medicaid . State limits on the eligibility and the extent of coverage through Medicaid affect management of liver disease, treatment of hepatitis C virus, and likelihood of being placed on the waiting list .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10th Amendment of the US Constitution is widely interpreted to reserve decisions of health policy within the rights of the state government rather than the federal government . A wide range of important and highly controversial health policies are regulated primarily at the state level, including abortion, vaccination, and physician‐assisted death, but the most vital and wide‐ranging of state‐level policies are public insurance programs, such as Medicaid . State limits on the eligibility and the extent of coverage through Medicaid affect management of liver disease, treatment of hepatitis C virus, and likelihood of being placed on the waiting list .…”
Section: Discussionmentioning
confidence: 99%
“…(22,23) A wide range of important and highly controversial health policies are regulated primarily at the state level, including abortion, vaccination, and physician-assisted death, but the most vital and wide-ranging of state-level policies are public insurance programs, such as Medicaid. (24)(25)(26)(27)(28) State limits on the eligibility and the extent of coverage through Medicaid affect management of liver disease, treatment of hepatitis C virus, and likelihood of being placed on the waiting list. (21,29,30) Beyond the statutory authority of states, there are practical considerations that support a statebased liver distribution scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Because the exemption process is heterogeneous, we accounted for the strength of state exemption policies (ie, whether it was "easy," "medium," or "difficult" for parents to claim an exemption) on the basis of standards previously reported by Omer et al 6 We chose this adjustment because previous studies suggest that nonmedical exemption rates decrease when exemption policies are more difficult to obtain. 5,19 Because many states revised their exemption laws during the study period, we recoded exemption law strengths for each state every year with published exemption law summaries. 1,6 We did not include Mississippi and West Virginia because they did not allow nonmedical exemptions.…”
Section: Methodsmentioning
confidence: 99%
“…The downstream impact of vaccination exemption policy on vaccination rates is also important to consider. Childhood vaccination rates tend to be lower in states with more permissive exemption policies [9], and a recent analysis has shown that in states allowing personal belief exemptions, higher levels of exemptions were associated with lower levels of measles, mumps, and rubella (MMR) vaccination in children attending kindergarten in the school year 20162017 [10]. Change in vaccination mandates increasing the difficulty for parents to obtain non-medical exemptions have had positive impacts on vaccination rates, including in Washington in 2011 [11] and California from the 2012-2013 school year [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, assessing the association between policy changes and non-medical exemption rates remains necessary in other states and policy contexts. The success of California in eliminating non-medical exemptions comes in contrast with several failed legislative attempts in other states [9], even though the legality of non-medical exemption bans similar to the one implemented in California is not in question [13]. This variation in the success of legislative actions in reducing non-medical exemption rates demands that we assess variations in rates over consecutive years, in different policy and epidemiological contexts.…”
Section: Introductionmentioning
confidence: 99%